Understanding the interplay between mild traumatic brain injury and cognitive fatigue: models and treatments - Glenn R Wylie; Laura A Flashman (Concussion, 2017)
Nearly 2 million traumatic brain injuries occur annually, most of which are mild (mTBI). One debilitating sequela of mTBI is cognitive fatigue: fatigue following cognitive work. Cognitive fatigue h...